Development of E-learning Teaching Materials Graphic Media Development Course for Students’ Educational Curriculum and Technology - Hari Sugiharto Setyaedhi; Andi Mariono; Alim Sumarno (Universitas Negeri Makassar, 2023)
This study aims at identifying the feasibility and efficacy of e-learning material for graphic media development subject by using the e-learning material provided by Universitas Negeri Surabaya. The study takes place in The Department of Technology of Education, Universitas Negeri Surabaya. The subject involves students who have participated in media graphic course. The samples are selected through simple random sampling with the amount of samples in experiment and control class is 30 students each. This development research is carried out using the development model of Four-D Model with the stages of Define, Design, Develop, Disseminate. The validation test on each unit of test proved that all of them are considered valid at Sig. 5%, while the reliability coefficient of the test is = 0.83. Feasibility test on the material and media each gains 88.5% and 87.7%, which means very feasible to apply. The effectiveness test on the e-learning material is conducted using quasi experimental group analysis technique. Based on the Independent sample t test, it was gained that (p < 0.05). N-Gain from the experiment class is 0.6 which categorized as fairly effective, while the N-Gain of the control class is 0.45 and perceived as less effective. The findings presented that e-learning material is deemed feasible and fairly effective to be used during the teaching and learning activity and could improve the students’ learning outcome.